Incidence and Determinants of Perinatal Mortality among Women with Obstructed Labour in Eastern Uganda: A Prospective Cohort Study - Musaba, Milton W. Musaba; Ndeezi, Grace; Barageine, Justus K.; Wandabwa, Julius N.; Mukunya, David; Waako, Paul; Odongkara, Beatrice; Arach, Agnes; Mugabe, Kenneth Tulya-muhika; Napyo, Agnes Kasede; Nankabirwa, Victoria; Tumwine, James K. (Maternal health, neonatology and perinatology, 2021)
In Uganda, the incidence and determinants of perinatal death in obstructed labour are not well documented. We determined the incidence and determinants of perinatal mortality among women with obstructed labour in Eastern Uganda. Between July 2018 and September 2019, 584 with obstructed labour were recruited and followed up to the 7th day postnatal. Information on maternal characteristics, obstetric factors and laboratory parameters was collected. Each patient received the standard perioperative care. We used a generalized linear model for the Poisson family, with a log link and robust variance estimation to determine the association between the exposure variables and perinatal death. Of the 623 women diagnosed with obstructed labour, 584 met the eligibility criteria. There were 24 fresh still births (FSB) and 32 early neonatal deaths (ENND) giving an FSB rate of 43.8 (95% CI 28.3–64.4) deaths per 1000 total births; early neonatal death rate of 58.4 (95% CI 40.3–81.4) deaths per 1000 and an overall perinatal mortality rate of 102.2 (95% CI 79.4–130.6) deaths in the first 7 days of life. A mother being referred in active labour adjusted risk ratio of 2.84 (95% CI: 1.35–5.96) and having high blood lactate levels at recruitment adjusted risk ratio 2.71 (95% CI: 1.26–4.24) were the determinants of perinatal deaths. The incidence of perinatal death was four times the regional and national average. Babies to women referred in active labour and those with high maternal blood lactate were more likely to die.